Coupled order parameters and photoinduced domain walls in the charge density wave of (TaSe4)2I - Ryan A. Duncan; Gal Orenstein; Soyeun Kim; Yijing Huang; Huaiyu Wang; Samuel W. Teitelbaum; Jade Stanton; Matthew Hurley; Alexander Miller; Nicholas Leonard; Dillon Hanlon; David A. Reis; et al. (npj Quantum Materials)
Abstract The charge density wave in (TaSe4)2I has drawn much attention recently as a controversial candidate for an axion insulator where the CDW breaks the chiral symmetry of the Weyl semimetal. Here we use ultrafast x-ray scattering to study the collective modes of this CDW. By measuring several diffraction peaks we find that the order parameter involves coupled optical and acoustic modes. For strong near-infrared excitation, the dynamics of the x-ray diffraction show evidence of photoinduced inversion of both components of the CDW order parameter, and associated domain walls. These results demonstrate the potential of ultrafast methods to induce topological defects through highly nonequilibrium dynamics. In (TaSe4)2I these defects should lead to exotic electronic states due to the nontrivial topology of the band structure.